The Relationship Between Students' Asking Activity and Critical Thinking Ability in Class VIII for Science Learning - Agustina, Wahyu Laila; Anggraini, Widra Dwi; Khasanah, Reni Rodhotul; Aristiawan (Program Studi Tadris IPA, Fakultas Tarbiyah (IAIN) Kediri, Indonesia, 2023)
One of the factors in students' actions that affects their level of critical thinking skills is their activeness in asking questions as a student's perspective to find answers to facts and certainty about some things that are not yet understood. This study aims to determine the relationship between the activeness of asking questions of class VIII students and the ability to think critically in science learning at Junior High School YP. KH. Syamsuddin Ponorogo. This research is quantitative and uses quantitative data analysis methods. Data collection techniques were carried out using questionnaires. The results of the study show that the significance value according to the test results is equal to 0.004, which indicates that the significance value is less than 0.05, so it can be concluded that there is a positive relationship or correlation; the more students are active in learning, the higher the critical thinking skills possessed by students. Vice versa, the lower the activity of students during learning, the lower their critical thinking skills will be.